Gender before birth : sex selection in a transnational context - Bhatia, Rajani (Feminist technosciences., 2018)
This book breaks new ground on the evolution and present technologies and practices of lifestyle sex selection, builds on and critiques feminist and STS theories of reproduction to develop the new concept of biopopulationism, and engages with the messy politics of sex selection in the United States.